Analysis of Landscape Impact on Post-Earthquake, Tsunami, and Liquefaction Disasters in Palu City, Central Sulawesi. Issue 1 (May 2020) - Darma, Y; Sulistyantara, B; Yonvitner,
Abstract: Sulawesi is an island that is affected by three main plate basins namely the Pacific Ocean plate, the Indo-Australian plate, and the Eurasian continent plate which produces several faults and causes intensive seismicity and other disasters in the region. Palu City as the Capital of Central Sulawesi Province is a disaster-prone area such as earthquake, tsunami and liquefaction. The impact of the disaster caused huge losses especially since the area has a high population. The importance of disaster mitigation plans in the area so that casualties, damage to public facilities, and other losses can be minimized. The mitigation plan consists of several stages namely the preparation, analysis, synthesis, and making the plan recommendations. Overall, Palu City is prone to disasters. The area that has a high level of vulnerability to 3 disasters has a total area of 446 hectares. Whereas for areas that have a high level of vulnerability to 2 disasters and 1 disaster has a total area of 3364 hectares and 3873 hectares respectively. There are 3 zones based on potential disasters in Palu City. Zone A is a zone that is prone to earthquake hazards. The total area of Zone A is 9100 hectares. Zone B is a zone for mangrove forest planting areas. The total area of Zone B is 572 hectares. Zone C is a zone that is prone to liquefaction hazards. The plant is expected to be able to absorb saturated ground water and reduce soil movement so it does not shift. The total area of Zone C is 1556 hectares. Disaster-prone areas are recommended to be relocated to safe areas in accordance with the recommended relocation locations. The recommended relocation area is on a flat slope of 6093 hectares and on a gentle slope of 5557 hectares.